Stability of cytokines, chemokines and soluble activation markers in unprocessed blood stored under different conditions. (August 2016) - Aziz, Najib; Detels, Roger; Quint, Joshua J.; Li, Qian; Gjertson, David; Butch, Anthony W.
Highlights: The stability of various biomarkers in unprocessed blood samples was investigated. IFN-γ, sIL-2Rα, sTNF-RII and β2 -microglobulin were found to be stable for 24 h. IL-6, TNF-α, MIP-1β, RANTES, IL-12 and IL-1ra were unstable under certain conditions. All the biomarkers studied, were stable in unprocessed EDTA blood stored at refrigerator temperature for 24 h. EDTA blood should be collected for biomarker testing with the exception of IL-1ra when processing is delayed. Abstract: Background: Biomarkers such as cytokines, chemokines, and soluble activation markers can be unstable when processing of blood is delayed. The stability of various biomarkers in serum and plasma was investigated when unprocessed blood samples were stored for up to 24 h at room and refrigerator temperature. Methods: Blood was collected from 16 healthy volunteers. Unprocessed serum, EDTA and heparinized blood was stored at room (20–25 °C) and refrigerator temperature (4–8 °C) for 0.5, 2, 4, 6, 8, and 24 h after collection before centrifugation and separation of serum and plasma. Samples were batch tested for various biomarkers using commercially available immunoassays. Statistically significant changes were determined using the generalized estimating equation. Results: IFN-γ, sIL-2Rα, sTNF-RII and β2 -microglobulin were stable in unprocessed serum, EDTA and heparinized blood samples stored at either room or refrigerator temperature for up to 24 h. IL-6, TNF-α, MIP-1β and RANTES were unstable in heparinized blood at room temperature; TNF-α, and MIP-1β were unstable in unprocessed serum at room temperature; IL-12 was unstable in unprocessed serum at refrigerator temperature; and neopterin was unstable in unprocessed EDTA blood at room temperature. IL-1ra was stable only in unprocessed serum at room temperature. Conclusion: All the biomarkers studied, with the exception of IL-1ra, were stable in unprocessed EDTA blood stored at refrigerator temperature for 24 h. This indicates that blood for these biomarkers should be collected in EDTA and if delays in processing are anticipated the unseparated blood should be stored at refrigerator temperature until processing.